Coffee and tea consumption, patient‐reported, and clinical outcomes in a longitudinal study of patients with breast cancer. Issue 19 (1st August 2022) - Soldato, Davide; Havas, Julie; Crane, Tracy E.; Presti, Daniele; Lapidari, Pietro; Rassy, Nathalie; Pistilli, Barbara; Martin, Elise; Del Mastro, Lucia; Martin, Anne‐Laure; Jacquet, Alexandra; Coutant, Charles; et al.
Abstract : Background: Higher consumption of coffee and tea has been associated with improved health outcomes in the general population and improved breast cancer (BC) prognosis. This study investigated patterns of coffee and tea consumption and association with patient‐reported outcomes (PROs) and clinical outcomes among survivors of BC. Methods: The authors included survivors of stage I–III BC enrolled in the CANTO cohort (NCT01993498) that provided post‐treatment assessment of coffee and tea consumption from years 1 to 4 after diagnosis. Group‐based trajectory modeling clustered patients according to daily consumption of coffee and tea. Multivariable mixed models and Cox models examined associations between consumption, PROs and clinical outcomes. Results: Among 3788 patients, the authors identified four stable patterns of consumption: "Low" (25.8%), "Moderate" (37.6%), "High" (25.3%), and "Very high" (11.3%), corresponding to <1, 2, 3, and ≥ 4 cups of coffee and/or tea per day. Patients in the "Very high" group (vs. "Low"), were more likely to be younger, smokers, with higher monthly income and education. PROs and survival outcomes were similar across the four groups. Conclusions: Over one in three survivors of BC reported high or very high consumption of coffee and/or tea. The authors found no association between higher consumption of coffee and/or tea, worse PROs and clinical outcomes. Abstract : More than 30% of survivors of breast cancer report high post‐diagnostic consumption of coffee and tea. In this study, the authors did not find any detrimental association between higher consumption of coffee and tea and patient‐reported or clinical outcomes.